2005
DOI: 10.1111/j.0105-2896.2005.00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of RANKL in physiological and pathological bone resorption and therapeutics targeting the RANKL–RANK signaling system

Abstract: Osteoclasts are primary cells for physiological and pathological bone resorption, and receptor activator of nuclear factor-kappaB ligand (RANKL) is critically involved in the differentiation, activation, and survival of these cells. Recently, therapeutics for pathological bone destruction targeting RANKL pathways has attracted a great deal of attention. Herein, we review the recent advances in the research on osteoclast biology and discuss the advantages and disadvantages of anti-RANKL therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
268
1
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 289 publications
(277 citation statements)
references
References 225 publications
(272 reference statements)
3
268
1
5
Order By: Relevance
“…It has been reported that Pax5-deficient mice exhibit osteopenia (25), a pathological condition in which osteoclasts are likely to be involved (39). Although Pax5 was detected only in the B cell lineage, and not in bone marrow macrophages nor in osteoclasts (40), the report nonetheless suggests that Pax5 or its related Pax family members may play a role in bone metabolism.…”
Section: Pax6 Expression During Rankl-induced Osteoclastogenesis-mentioning
confidence: 76%
“…It has been reported that Pax5-deficient mice exhibit osteopenia (25), a pathological condition in which osteoclasts are likely to be involved (39). Although Pax5 was detected only in the B cell lineage, and not in bone marrow macrophages nor in osteoclasts (40), the report nonetheless suggests that Pax5 or its related Pax family members may play a role in bone metabolism.…”
Section: Pax6 Expression During Rankl-induced Osteoclastogenesis-mentioning
confidence: 76%
“…(1,2) The imbalance between osteoblast and osteoclast activity underlies various bone and joint diseases, such as osteoporosis and rheumatoid arthritis. (3)(4)(5)(6) Osteoclasts are multinucleated giant cells that are polarized and resorb bone through specialized machinery so as to attach to mineralized matrix and degrade it. The differentiation of monocyte/ macrophage-lineage precursor cells into mature osteoclasts is induced by the tumor necrosis factor (TNF) family cytokine receptor activator of NF-kB ligand (RANKL) together with colonystimulating factor (M-CSF), and provides an activating signal as well as survival signals to osteoclasts.…”
Section: Introductionmentioning
confidence: 99%
“…It also binds to activated RANK (9), thereby recruiting TRAF6 and Grb2-associated binder 2 (Gab2) followed by phosphorylation of I B␣ and JNK (10), which ultimately lead to respective activation of the transcription factors NF-B and AP-1 (2,11,12).…”
mentioning
confidence: 99%